Novel configuration of supercritical water gasification and chemical looping for highly-efficient hydrogen production from microalgae. (September 2019) - Nurdiawati, Anissa; Zaini, Ilman Nuran; Irhamna, Adrian Rizqi; Sasongko, Dwiwahju; Aziz, Muhammad
Abstract: This study proposes a novel system to efficiently produce hydrogen from microalgae, based on supercritical water gasification and syngas chemical looping, and its conversion to methylcyclohexane. The process consists of a gasifier, a syngas chemical looping reactor, and a methylcyclohexane synthesis reactor as the main units. Microalgae are converted to syngas in the supercritical water gasification reactor. Thereafter, the produced syngas is introduced into the syngas chemical looping module to produce pure hydrogen and a separated carbon dioxide stream. The hydrogen is then reacted with toluene through the hydrogenation reaction to produce methylcyclohexane as a hydrogen carrier. The heat released from the methylcyclohexane synthesis module and chemical looping combustor is utilized to sustain the thermal balance of the supercritical water gasification unit. The system performance is observed under different feed moisture contents, operating temperatures in the supercritical water gasification unit, and operating pressures in the syngas chemical looping unit. A steady-state process simulation of Aspen Plus software is used for this purpose. The proposed integrated system exhibits of approximately 13.7%, 45.3%, and 59.1% for power generation efficiency, hydrogen production efficiency, and total energy efficiency, which demonstrates an efficient process of hydrogen production. The preliminary economic assessment shows that more than half of the operating cost accounts for microalgae production. This indicates the microalgae feedstock is one of the critical cost drivers in the microalgae-to-hydrogen production system. Highlights: Microalgae is converted into H2 and stored in the form of methylcyclohexane. The system combines supercritical water gasification (SCWG) and chemical looping. The process is simulated under different feed moisture contents and SCWG condition. The effect of moisture content shows different trends at different SCWG temperatures. High H2 production and total energy efficiencies can be obtained.